India towards 1990s - Mishra, R. K. . (New Delhi : Patriot Publishers, 1986)
On political and economic aspects; contributed articles.
Includes bibliographical references.
Keywords: Economic forecasting -- India; India -- Politics and government -- 1977-; India -- Economic conditions -- 1947-